Precoding design for STBC-MIMO system with imperfect feedback in spatially correlated Rayleigh channel - Xu, Weiye; Bao, Yongqiang; Yu, Xiangbin (Electronics letters, 2014)
By minimising the pairwise error probability (PEP) bound subject to the fixed power constraint, a suboptimal precoding scheme for space–time block-coded multiple-input–multiple-output (STBC-MIMO) systems with mean and covariance feedback in spatially correlated Rayleigh fading channels is developed, which can include the mean-feedback only and covariance-feedback only as its special cases. This scheme can achieve performances close to the existing optimal scheme while being more computationally efficient. The simulation results show that the proposed scheme can provide better performances than the conventional equal power scheme, and achieve almost the same performances as the existing optimal scheme.